Interleukin‐36α axis is modulated in patients with primary Sjögren's syndrome. (3rd June 2015) - Ciccia, F.; Accardo‐Palumbo, A.; Alessandro, R.; Alessandri, C.; Priori, R.; Guggino, G.; Raimondo, S.; Carubbi, F.; Valesini, G.; Giacomelli, R.; Rizzo, A.; Triolo, G.
Summary The aim of this study was to investigate the expression of the interleukin (IL)‐36 axis in patients with primary Sjögren's syndrome (pSS). Blood and minor labial salivary glands (MSG) biopsies were obtained from 35 pSS and 20 non‐Sjögren's syndrome patients (nSS) patients. Serum IL‐36α was assayed by enzyme‐linked immunosorbent assay (ELISA). IL‐36α, IL‐36R, IL‐36RA, IL‐38, IL‐22, IL‐17, IL‐23p19 and expression in MSGs was assessed by reverse transcription–polymerase chain reaction (RT–PCR), and tissue IL‐36α and IL‐38 expression was also investigated by immunohistochemistry (IHC). αβ and γδ T cells and CD68+ cells isolated from MSGs were also studied by flow cytometry and confocal microscopy analysis. IL‐36α was over‐expressed significantly in the serum and in the salivary glands of pSS. Salivary gland IL‐36α expression was correlated with the expression levels of IL‐17, IL‐22 and IL‐23p19. IL‐38, that acts as inhibitor of IL‐36α, was also up‐regulated in pSS. αβ+ CD3+ T cells and CD68+ cells were the major source of IL‐36α in minor salivary glands of pSS. γδ T cells were not significantly expanded in the salivary glands of pSS but produced more IL‐17, as their percentage correlated with the focus score. Higher expression of IL‐36α and IL‐36R was also demonstrated in γδ T cells isolated from pSS compared to controls. In this study we demonstrate that a significant increase in circulating and tissue levels of IL‐36α occurs in pSS patients.